IgE Levels to Ascaris and House Dust Mite Allergens Are Associated With Increased Histone Acetylation at Key Type-2 Immune Genes - Zakzuk, Josefina; Acevedo, Nathalie; Harb, Hani; Eick, Lisa; Renz, Harald; Potaczek, Daniel P.; Caraballo, Luis (Frontiers in Immunology, 2020)
Background: Epigenetic changes in response to allergen exposure are still not well understood. The aim of this study was to evaluate histone acetylation levels in peripheral blood leukocytes from humans naturally infected by intestinal parasites and perennially exposed to house dust mites (HDM). Methods: Peripheral blood mononuclear cells (PBMCs) were isolated by gradient centrifugation from 20 infected and 21 non-infected individuals living in a rural/village in Colombia. Histone 3 acetylation (H3Ac) and histone 4 acetylation (H4Ac) levels were measured in six immune genes previously associated with helminth immunity by chromatin immunoprecipitation (ChIP)-quantitative PCR. Then we analyzed the association between histone acetylation levels with total parasite egg burden and IgE levels. Results: We found an inverse correlation between H4Ac levels in the IL13 gene and egg worm burden that remained significant after adjustment by age [-0.20 (-0.32 to -0.09), p < 0.0001]. Moreover, we found significant associations between H4Ac levels in IL4 [0.32 (0.05 – 0.60), p = 0.02] and CHI3L1 [0.29 (0.08 – 0.51), p = 0.008] with the IgE levels to Ascaris lumbricoides. In addition, the levels of specific IgE antibodies to HDM were associated with H4Ac levels in the gene TNFSF13B encoding the B cell activating factor (BAFF) [0.51 (0.26-0.76), p < 0.001]. Conclusion: Histone acetylation levels at key type-2 immune genes in humans were modified by nematode infection and HDM allergens and are associated with the intensity of the IgE response.